The Acute Exercise-Induced Inflammatory Response: A Comparison of Young-Adult Smokers and Nonsmokers. Issue 1 (2nd January 2017) - Kastelein, Tegan E.; Donges, Cheyne E.; Mendham, Amy E.; Duffield, Rob
Abstract : Purpose: This study examined postexercise inflammatory and leukocyte responses in smokers and nonsmokers, as well as the effects of cigarette smoking on the acute postexercise inflammatory and leukocyte response in habitual smokers.Method: Eleven recreationally active male smokers and 11 nonsmokers matched for age and aerobic fitness were familiarized and underwent baseline fitness testing. Participants then completed 40 min of cycling at 50% peak aerobic workload. Smokers performed 2 randomized exercise sessions, including an acute postexercise smoking condition (2 cigarettes in 15 min of 12 mg tar and 1 mg nicotine) and a no-smoking condition, while nonsmokers performed 1 exercise session without smoking. Venous blood was obtained preexercise and postexercise for analysis of interleukin (IL)-6, IL-1 receptor antagonist (ra), tumor necrosis factor-alpha (TNF-α), and c-reactive protein (CRP).Results: No differences existed between groups for resting CRP ( d  = 0.25–0.46; p  = .374–.617). Despite no baseline difference ( d  = 0.03–0.07; p  = .141–.70), exercise-induced increases were observed for IL-1 ra in smokers ( d  = 0.50; p  = .024–.033), which was not observed in the never-smoker group. No between-group difference was observed for IL-6 across all points ( d  = 0.09–0.5; p  = .102–.728); however, all groups observed significant within-group change ( d  = 0.27–1.09; p  = .001–.042). Further, TNF-α for smokers smoking was elevated above both smokers not smoking and nonsmokers at baseline and across the protocol ( d =  1.20–1.80; d =  0.20–1.0; p  = .001–.035). Additionally, a marked postexercise increase in leukocyte and neutrophil concentrations was evident in smokers smoking compared with nonsmokers and smokers not smoking as indicated by a moderate-to-large effect size ( d =  0.72; d =  0.78).Conclusion: Consequently, male smokers exhibit an altered postexercise proinflammatory profile compared with age- and fitness-matched nonsmokers.